A laptop for every child? The impact of ICT on educational outcomes - Caroline Hall; Martin Lundin; Kristina Sibbmark (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2019)
Classrooms all over the world are becoming increasingly technologically advanced. Many schools today provide a personal laptop or tablet to each pupil for use both in the classroom and at home. The intent of these 1:1 programs is that information and communication technology (ICT) should be extensively involved in the teaching of all subjects. We investigate how pupils who are given a personal laptop or tablet, rather than having more limited computer access, are affected in terms of educational performance. By surveying schools in 26 Swedish municipalities regarding the implementation of 1:1 programs and combining this information with administrative data, we estimate the impact on educational outcomes using a difference-in-differences design. We find no significant impact on standardized tests in mathematics or language on average, nor do we find an impact on the probability of being admitted to upper secondary school or the students' choice of educational track. However, our results indicate that 1:1 initiatives may increase inequality in education by worsening math skills and decreasing enrollment in college-preparatory programs in upper secondary school among students with lower educated parents.
Keywords: I21; 330; technology; computers; one-to-one; student performance